The Precautionary Principle In The Transfer Of Trademark Rights By Notaries - Fenny Riski Diana; Gunardi Gunardi (Jurnal Indonesia Sosial Teknologi, 2023)
The outcome of business activities in the field of services or trade can be identified as a trademark or service mark. The term "trademark" refers to a symbol that can be in the form of a picture, name, numbers, color arrangement, or a combination of these elements, possessing the ability to distinguish and be used in the trade of goods or services. Trademarks are intangible entities that can be transferred, including through agreements transferring ownership rights to the trademark. In the context of a trademark transfer, a notary plays a role in drafting the transfer deed. The purpose of this research is to comprehend and analyze the notary's role in the preparation of trademark transfer deeds and evaluate the notary's responsibility in providing legal protection to the parties involved, considering the intangible nature of trademarks. Legal data collection techniques involve primary and secondary legal materials. The research method employed is a normative juridical approach with legislative and conceptual perspectives. Based on the research findings, it is revealed that the principle of caution is one of the key principles that must be followed or adhered to by a notary in the execution of their duties.